Psychometric properties of the wellbeing literacy 6-item scale in Chinese military academy cadets - Jia, Zhen; Zheng, Fangfang; Wang, Feifei; Yang, Guoyu (Frontiers in Psychology, 2024)
Background: Positive psychology is a vibrant field of study, and conceptualizations of the components of well-being have received a great deal of attention from researchers. The study of well-being literacy thus provides an innovative perspective for enhancing and sustaining individuals' experiences of well-being.Objective：This study aimed to examine the psychometric properties of the wellbeing literacy 6-item (Well-Lit 6) scale in Chinese military academy cadets.Methods: A total of 3218 undergraduate students from five military academies in China were recruited to complete questionnaires online.(1) The items of the scale showed high discrimination; (2) The alpha coefficient of the scale was 0.986 and the split-half reliability was 0.981, indicating high homogeneous